Disparities Predict for Higher Rates of Cut-through Hysterectomies in Locally Advanced Cervical Cancer. (January 2019) - Amini, Arya; Robin, Tyler P.; Rusthoven, Chad G.; Schefter, Tracey E.; Akhavan, David; Chen, Yi-Jen; Glaser, Scott M.; Corr, Bradley R.; Ashing, Kimlin T.; Fisher, Christine M.
Abstract : Objectives: The treatment of choice for locally advanced cervical cancer is definitive chemoradiation (CRT). Hysterectomy is not indicated due to higher-rates of cut-through resections leaving gross disease behind, requiring additional therapy with increasing morbidity and no benefit in overall survival (OS). The objectives of this study were to determine factors associated with cut-through hysterectomies and evaluate OS outcomes. Materials and Methods: The National Cancer Database (NCDB) was queried for patients 18 years and older with clinical Federation of Gynecology and Obstetrics stage IB2 to IVA. All patients underwent upfront hysterectomy and had known margin status. Cut-through hysterectomy was classified as presence of microscopic or macroscopic disease at the margin. Results: A total of 11, 638 patients were included; 993 (8.5%) had positive margins. In patients with positive margins, 560 (56.4%) received postoperative CRT and 148 (14.9%) underwent postoperative radiation. Five-year OS was worse for those with cut-through resections when compared with those with negative margins, 66.0% versus 86.7%, respectively (hazard ratios, 3.08; P <0.001). Under multiple logistic regression, African American race (odds ratio [OR], 1.45; P= 0.001), older age (OR per year increase, 1.03; P <0.001), patients with government insurance (OR, 1.21; P= 0.019), and those treated at community practices (OR, 1.31; P= 0.001) were more likely to undergo cut-through hysterectomies. Conclusions: A review of national patterns of care over the past decade confirms women with positive margins after hysterectomy for cervical cancer have significantly worse OS. Disparities in surgical results for women with cervical cancer exist. In response, further causality evaluation and corrective action are warranted to address these inequalities.